An interprofessional community education project as a socially accountable assessment. Issue 5 (28th August 2015) - Gallagher, Peter; Pullon, Sue; Skinner, Margot; McHugh, Patrick; McKinlay, Eileen; Gray, Lesley
Abstract: As part of a clinically based rotational undergraduate interprofessional programme, an assessment was devised which was construed as being socially accountable. An interprofessional programme, with cohorts of students from six different health professions, was evaluated in a number of ways. Students completed pre and post questionnaires about many aspects of the programme and also participated in focus groups. The social accountability of the key assignment emerged as important for both students and the community agencies that provided the clinical experience for students. Students implicitly and explicitly reported that their awareness of the need for health professionals to be socially accountable was heightened as a result of the assignment task. This article indicates that with creativity and perseverance an assessment can be devised that is relevant both to the student and the community, and is a powerful learning exercise for all involved.